Analisis Faktor-Faktor Motivasi Kerja dalam Meningkatkan Kinerja Karyawan - Adi Yasin Maulana Azis; Imam Khairuddin; Dimas Arfiansyah Putra; Ahmad Junaidi; Septian Bayu Arief (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Employee work motivation stands as a pivotal aspect capable of significantly enhancing employee performance within any organizational setting. This qualitative study endeavors to comprehensively gather information regarding the multifaceted factors that influence employee work motivation, ultimately impacting their overall performance. Utilizing a qualitative research methodology with a robust literature review approach, this investigation systematically reviews and synthesizes findings from an array of prior studies. The synthesis of our findings reveals two primary categories of factors critically affecting employee work motivation: external and internal factors. External factors encompass crucial elements such as the work environment, salary structures, the quality of supervisor treatment, and prevailing company policies. Conversely, internal factors primarily involve an individual's personal desires and inherent needs that require fulfillment within the employee. In light of these findings, it is imperative for organizations to address and fulfill these identified factors, particularly external ones, as a strategic endeavor to elevate and sustain employee performance.